Improving Pre-emptive Prescribing to Relieve Patient Discomfort Occurring Out of Hours. Issue 1 (12th February 2016) - Williams, Rhys; Herbert, Fiona; Orme, Amy; Casswell, Georgina
Abstract: Junior doctors are commonly asked to prescribe simple medications for symptom relief for patients out of hours. Unfortunately, time constraints and other pressures may lead to delays before the medications are prescribed. A quality improvement project was conducted at a large university teaching hospital to establish the extent of the problem, with the aim of finding measures to improve preemptive prescribing for patients. Baseline data was gathered over three busy wards to calculate the total of new prescriptions made over the course of a weekend. There were 24 new prescriptions required over the weekend, a percentage increase of 14.9% compared to the existing prescriptions on a Friday. Following the first intervention this decreased to 10.2%, and by the second intervention the rate was 4.9%. Data collected several months later confirmed that the interventions remained successful, and preemptive prescribing continued. Overall, our interventions have shown that the number of new prescriptions required out of hours can be reduced by educating junior doctors on preemptive prescribing.